Analysis of Forest Encroachment in Bukit Barisan Selatan National Park (Study case in Tirom Village, Pematang Sawa Sub Regency, Tanggamus Regency) - Deni Deni (Jurnal Ilmu Kehutanan)
Most of National Parks in Indonesia have their problems related to human existence in conservation area. Since its establishment, there has been a conflict between Bukit Barisan Selatan National Park (BBSNP) with the surrounding communities. In the BBSNP, there have been acts of illegal landusage where it is commonly referred as forest encroachment. Forest encroachment in Tirom village is becoming interesting to study because it needs more complicated handling compared to other villages.